Markers of obesity and growth in preeclamptic and normotensive pregnant women. (4th July 2017) - Kharb, S.; Bala, J.; Nanda, S.
Abstract: The objective of the study was to analyse leptin, IGF-1, Apo A, lipoproteins, haem oxygenase-1 (HO-1) in maternal sera and venous umbilical cord sera of newborn babies of 25 preeclamptics (group II), and 25 normotensive pregnant women (group I) as markers of obesity and growth in preeclamptic and normotensive pregnant women. Apo A I and II levels were estimated by competitive immunoassay using direct chemiluminiscence technology. Haem oxygenase-1 (HO-1), leptin and IGF-1 were analysed by ELISA. Maternal and cord blood levels of homocysteine, folic acid, lipid profile (namely, total cholesterol, triglycerides, LDL-C, VLDL-C and HDL-C), Haem oxygenase 1 were higher in preeclamptic women as compared to normotensive pregnant women. Serum and cord blood Apo A-I and Apo B, leptin levels, IGF-I were lower in preeclamptic women as compared to normotensive pregnant. The findings of high serum HO-1 levels in maternal and cord blood in preeclampsia supports the role of oxidative stress and excessive inflammatory response in the pathogenesis of preeclampsia. It seems likely that IGF-1 and leptin play a central role in controlling foetal growth. There is increasing evidence that the foundations of life-long health are, in part, laid in the uterus. Findings of present study suggest that alterations in biochemical markers of growth and obesity occur in mothers and foetuses and modifications of uterine environment can be of help to prevent future cardiovascular risk. Impact statement: Preeclampsia has been reported to be associated with an increased risk of later life cardiovascular disease. However, information regarding how obesity increases the risk of preeclampsia is limited. Atherogenic milieu occurring during pregnancy persists into adulthood and foetal growth retardation is strongly associated with adult atherosclerosis. There is conflicting evidence regarding alterations of IGFs in preeclamptic pregnancies and deficit in circulating and cord blood IGF-1 levels in intrauterine growth restricted newborns and a correlation between IGF-1 levels and birth weight have been reported. Leptin is a predictor of cardiovascular risk independent of insulin resistance. Emerging evidence supports an important role for the haem oxygenase system (HO-1) in the maintenance of a healthy pregnancy, especially during pathological challenge. Conflicting data are available regarding HO-1, leptin and IGF –1 in preeclamptic mothers. The extent to which they mediate foetal growth and developmental abnormalities remains to be clarified. Serum IGF-1 levels were significantly decreased in preeclamptics and maternal IGF-1 showed a strong inverse correlation with leptin levels. High serum HO-1 levels in maternal and cord blood in preeclampsia were observed in the present study. Findings of the present study suggest that alterations in biochemical markers of growth and obesity occur in mothers and foetuses and modifications of the uterine environment can be of help to prevent future cardiovascular risk.